Diblock Polyelectrolytic Copolymers Containing Cationic Iron and Cobalt Sandwich Complexes: Living ROMP Synthesis and Redox Properties. Issue 7 (3rd February 2016) - Gu, Haibin; Ciganda, Roberto; Hernandez, Ricardo; Castel, Patricia; Zhao, Pengxiang; Ruiz, Jaime; Astruc, Didier
Abstract : Diblock metallopolymer polyelectrolytes containing the two redox‐robust cationic sandwich units [CoCp′Cp] + and [FeCp′(η 6 ‐C6 Me6 )] + (Cp = η 5 ‐C5 H5 ; Cp′ = η 5 ‐C5 H4 ‐) as hexafluorophosphate ([PF6 ] − ) salts are synthesized by ring‐opening metathesis polymerization using Grubbs' third generation catalyst. Their electrochemical properties show full chemical and electrochemical reversibilities allowing fine determination of the copolymer molecular weight using Bard–Anson's electrochemical method by cyclic voltammetry. Abstract : Diblock polyelectrolytes containing both iron and cobalt electron‐reservoir sandwich complexes in their cationic forms are synthesized by living ring‐opening metathesis polymerization (ROMP) with Grubbs' third generation catalyst and possess a rich redox chemistry. The full chemical and electrochemical reversibilities of the distinct cathodic cyclovoltammetry waves allow to determine the number of monomer units of each metalloblock.